Quality of analgesia after lower third molar surgery: A randomised, double-blind study of levobupivacaine, bupivacaine and lidocaine with epinephrine - Brajković, Denis Oliver; Biočanin, Vladimir; Milić, Marija; Vučetić, Milan; Petrović, Renata; Brković, Božidar (Vojnosanitetski pregled, 2014)
Background/Aim. Surgical extraction of lower third molars is followed by mild or severe postoperative pain which peaks at maximal intensity in the first 12 hours and has a significant impact on a patient’s postoperative quality of life. The use of long-acting local anaesthetics is a promising strategy to improve postoperative analgesia. The aim of the present study was to investigate analgesic parameters and patient satisfaction after using 0.5% levobupivacaine (Lbup), 0.5% bupivacaine (Bup) and 2% lidocaine with epinephrine 1:80,000 (Lid + Epi) for an inferior alveolar nerve block following lower third molar surgery. Methods. A total of 102 patients (ASA I) were divided into three groups, each of which received either 3 mL of Lbup, Bup or Lid + Epi. The intensity of postoperative analgesia was measured using a verbal rating scale (VRS). The total amounts of rescue analgesics were recorded on the first and during seven postoperative days. Patients satisfaction was noted using a modified verbal scales. Results. A significantly higher level of postoperative pain was recorded in Lid + Epi group compared to Bup and Lbup groups. No significant differences were seen between Bup and Lbup, but a significant reduction in the need for rescue analgesics was seen postoperatively in both Lbup and Bup (50%) in comparison with Lid + Epi (80%) in the first 24 hours. The same significant trend in rescue analgesic consumption was recorded for seven postoperative days. Patients’ overall satisfaction was significantly lower for Lid + Epi (10%) than for Lbup (56%) and Bup (52%). Conclusion. The use of a new and long-acting local anaesthetic 0.5% levobupivacaine is clinically relevant and effective for an inferior alveolar nerve block and postoperative pain control after third molar surgery. In our study Lbup and Bup controled postoperative pain more efficiently after lower third molar surgery compared to Lid + Epi.
Keywords: tooth extraction; molar; third; bupivacaine; lidocaine; anesthesia; dental; pain; postoperative; questionaires